The Effect of Siskeudes Application Utilization, Operator Understanding Level, and Training on the Quality of Village Budget Reports in Torgamba District - Dea Sulistiawati; Laylan Syafina (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the influence of the utilization of the Village Financial System (Siskeudes) application, operator understanding, and training on the quality of Village Revenue and Expenditure Budget (APBDes) reports in Torgamba District, while also highlighting the importance of human resource capacity in strengthening transparency and accountability in village financial management. This research employed a quantitative approach using a survey method involving 34 village financial management officials as respondents. Data were analyzed using multiple linear regression with the assistance of SPSS. The results revealed that partially, operator understanding and training had a positive and significant effect on the quality of APBDes reports, whereas the utilization of the Siskeudes application did not show a significant effect. Simultaneously, all independent variables significantly affected report quality, with a coefficient of determination (R²) of 0.834 and an F-value of 50.217, indicating that 83.4% of the variation in APBDes report quality could be explained by the proposed model. These findings demonstrate that the quality of village financial reports is influenced more by the competence and training of officials than by the mere use of information systems. The study contributes to the literature on village financial governance by emphasizing the strategic role of capacity-building programs in improving the effectiveness of Siskeudes implementation and ensuring accountable village financial reporting.